Chapter 2. Fertilizer Management for Vegetable Production in Florida: CV296, rev. 4/2021 - Liu, Guodong; Simonne, Eric H.; Morgan, Kelly T.; Hochmuth, George J.; Agehara, Shinsuke; Mylavarapu, Rao; Williams, Phillip B. (EDIS, 2021)
Chapter 2 of the Vegetable Production Handbook